Cognitive impairment in primary hyperparathyroidism - N. G. Mokrysheva; Yu. A. Krupinova; E. E. Bibik; G. A. Melnichenko (Неврология, нейропсихиатрия, психосоматика)
Cognitive impairment (CI) is a nonclassical manifestation of primary hyperparathyroidism associated with impaired calcium and phosphorus metabolism. The pathophysiological mechanisms of cognitive dysfunction in this endocrine disease have not been fully elucidated. Nonetheless, studies have demonstrated neuropsychological improvements and better quality of life in patients who have achieved normocalcemia with reduced parathyroid hormone levels after surgical treatment for hyperparathyroidism. Further large-scale controlled studies are needed to determine the possibility of using neuropsychiatric complications as indications for parathyroidectomy.